2009
DOI: 10.5458/jag.56.153
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Microwave Irradiation on Water-soluble Polysaccharides of the Fruiting Body of Hericium erinaceum

Abstract: To examine the applicability of microwave irradiation for the extraction of polysaccharides in the fruiting body of Hericium erinaceum, structures of polysaccharides obtained by microwave irradiation in water were compared to those obtained by hot water extraction using conventional external heating. A major polysaccharide obtained by microwave irradiation in water (140 C, 5 min) was (1 3;1 6)-β-D glucan rich in (1 3) linkages, whereas polysaccharides obtained by hot water extraction using conventional externa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…8) We are, therefore, interested about β glucans in H. erinaceum and previously reported about extractability of β glucans from its pulverized fruiting body by using microwave heating in water. 9) The results showed that only 22.0% of β glucans were extracted by this treatment. The reason of this low extractability of β glucans may be due to their complex distribution in cell wall.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…8) We are, therefore, interested about β glucans in H. erinaceum and previously reported about extractability of β glucans from its pulverized fruiting body by using microwave heating in water. 9) The results showed that only 22.0% of β glucans were extracted by this treatment. The reason of this low extractability of β glucans may be due to their complex distribution in cell wall.…”
mentioning
confidence: 87%
“…10) In the case of Hericium erinaceum, so far Wang et al . extracted (1 6) 12) Our previous results further showed the presence of water soluble (1 3;1 6) β D glucan extractable by microwave irradiation in water 9) and alkali soluble (1 3;1 6) β D glucan having (1 6) linked branch points at every five (1 3) linked glucose residues. 13) Use of alkali was shown to be effective for extraction of glucans amounting to 42.3% of the total quantity in H. erinaceum.…”
mentioning
confidence: 99%
“…Due to different preparation methods, the structure, molecular weight, and other properties of the resulting Hericium erinaceus polysaccharides can also vary greatly. In terms of solubility, are they mainly water-soluble and alkali-soluble, in terms of molecular weight, their order of magnitude is in the range of 105-106, and in terms of structure, they mainly consist of β-(1→3) and β-(1→6)-glycosidic bonds, in which the molar ratio of the two types of glycosidic bonds differs greatly [22][23][24][25][26]. The significant structural differences in the β-glucan of Hericium erinaceus can be used as an ideal representative of the β-glucan of edible bacteria, providing a good model for studying the effect of different preparation methods and different structures on the regulation of the species structure of human fecal intestinal flora.…”
Section: Introductionmentioning
confidence: 99%